Bio-inspired mechanically robust superhydrophobic polypropylene surfaces embedded with silicon carbide whiskers for enhancing bactericidal performance - Jindi Lai; Anfu Chen; Jing Li; Yameng Pei; Seyed Ataollah Naghavi; Caihong Lei; Chaozong Liu; Lijia Huang (Journal of Materials Research and Technology, 2023)
The risk of spread of antibiotic-resistant bacteria leads to the growth of implant-associated infection, necessitating the large-scale fabrication of antibacterial materials. The successfully synthetic superhydrophobic and bactericidal materials without durable surfaces are easy to destroy and so difficult to use in a large-scale production in terms of manufacturing costs in performing experiments and processes. In this work, two kinds of microfeatured sieves dipped with high length-diameter ratio silicon carbide whiskers (SiCw) are used as templates for the fabrication of micropillared polypropylene (PP) surfaces embedded with nanospiked SiCw exposed in different postures of standing via a simple low-cost micro-compression molding method. The standing SiCw nanospikes endow the micropillared PP surfaces with a high contact angle (CA) of 153.9° decreased by less than 8° after a wear distance of 1500 mm, exhibiting robust antiwetting and antifriction properties. Further, the nanospiked micropillared PP surfaces exhibit extremely low adhesion and moderate antibacterial efficacy. The micro-/nanoconstructed PP surfaces is expected to approach towards large-scale industrial production for biomedical applications.